Cele polityki leśnej w Polsce w świetle aktualnych priorytetów leśnictwa w Europie Część 4. Trendy w polityce leśnej wybranych państw europejskich - Kaliszewski, Adam (Leśne Prace Badawcze, 2018)
The aim of this paper was to review and analyse the main forest policy documents in terms of the priorities formulated at the European level for Austria, the Czech Republic, Slovakia, Germany (federal level) and Brandenburg (federal state level), as well as Finland. A total of 14 documents was covered in this research, including national forest programmes and forest strategies implemented in the period from 1997 to 2017. In all of the studied countries, forest policy documents were periodically revised and updated to account for changing political, economic, social and environmental conditions. As a result, at some point during the examined 20-year period, in each country the forestry priorities and goals were defined by a national forest programme. Furthermore, the vast majority of the priorities set by the European forest policy was reflected in the programmes and strategies of all the countries. Certain priorities concerning the illegal harvesting and trade of forest products, however, have not been included in the explored documents. Combating illegal harvesting of forest products and related trade is a corner stone of the EU FLEGT Action Plan and extends beyond forest policy issues of EU member states. The second corner stone is to ensure the contribution of the forest sector to a green economy, including a new concept of green economy, which still needs to be incorporated into national forest policies. Unlike Poland, in the studied countries the priorities of European forest policy have been included in single policy programmes or strategies, which define aims and goals, as well as means of their implementation in a comprehensive and coherent manner. This promotes strengthening the position of the forest sector within the national socio-economic system and supports active shaping of its relations to other sectors of the economy.